Restorative proctocolectomy for distal ulcerative colitis. Issue 4 (1st October 1999) - Brunel, M; Penna, C; Tiret, E; Balladur, P; Parc, R
Abstract : BACKGROUND: Chronic distal colitis may cause troublesome symptoms and alter quality of life. When medical treatment fails to control symptoms, patients and doctors are often reluctant to consider surgical resection because of the relatively small portion of the large bowel affected by the disease. AIM: To assess the outcome of restorative proctocolectomy (RP) in patients with distal colitis who required surgery for chronic debilitating symptoms and failed medical management. PATIENTS/METHODS: From 1986 to 1996, of 263 patients receiving RP for ulcerative colitis, 27 (16 men) were operated on for distal ulcerative colitis limited to the rectum and sigmoid colon. Bowel function and quality of life were compared before and one year after RP. RESULTS: The mean (SD) duration of ulcerative colitis was 11 (6) years. RP was performed at a mean age of 46 (10) years. All the pouches were J-shaped, and a diverting loop ileostomy was always performed. Mean (SD) hospital stay was 25 (10) days. Seven complications occurred in six patients. Previously unknown severe dysplasia was discovered on the colectomy specimen in two patients. After RP there was a significant decrease in mean (SD) daytime stool frequency (8.2 (4) v 4.7 (2), p<0.05), night-time stool frequency (2 (2) v 1 (1), p = 0.05), and the number of patients with urgency to defecate (26/27 v 1/27, p<0.001). Sex life was improved in eight patients, social life in 26, and professional life in eight. Twenty six patients were satisfied with the results, and 25 wished that they had received surgery earlier in the course of their disease. CONCLUSION: RP can improve bowel function and quality of life in patients with disabling chronic symptoms of distal ulcerative colitis.